Capillary pressure in the anisotropy of sediments with hydrate formation. (1st April 2021) - Wang, Jiaqi; Zhang, Lunxiang; Ge, Kun; Dong, Hongsheng
Highlights: Capillary pressures in different directions are presented in this study. Hydrate formation makes the skewness of capillary pressure finer slanting degrees. The heterogeneity in hydrate formation determines capillarity in anisotropy. The stronger capillary heterogeneity occurs in the vertical direction. Abstract: The random nucleation and growth of hydrates in the pore space contribute to the heterogeneity of hydrate sediments, which results in anisotropic fluid flow. An exact forecast for capillary pressure in different directions, which governs the gas/water distribution and the volume of residual water saturation in porous sediments, is of significant importance for hydrate exploitation. In this study, the index properties of the artificial hydrate sediment were characterized through X-ray computed tomography (CT) visualization scanning. The spatial structure feature of hydrate sediment was captured via a topological pore network, which was established from CT imaging. Then, the evolution of capillary pressure in anisotropy with the formation of hydrates was simulated and discussed. The results indicated that with hydrate formation, the capillary pressure curves became steeper, representing skewness with finer slanting degrees and poor sorting. Moreover, the differences in capillary pressure with the same hydrate saturation between different directions was enlarged. Stronger capillary heterogeneity in the vertical direction represents greater heterogeneity, according to the Leverett J-Function.